PERAN PESANTREN ANNUQAYAH SEBAGAI DESTINASI WISATA HALAL BERBASIS KEARIFAN LOKAL DI MADURA DALAM PENINGKATAN PEREKONOMIAN MASYARAKAT - Salsabillah, Dhinda; Noor Hasan, Dony Burhan (Al-Musthofa: Journal of Sharia Economics, 2022)
The purpose of this research is to find out how the role of Annuqayah Islamic Boarding School as a halal tourismdestination based on local wisdom in Madura is to improve the community’s economy. This research was conductedat the Annuqayah Islamic Boarding School, Guluk-Guluk, Sumenep by involving caregivers, head of BPM, andthe community. This type of research uses qualitative methods which include interviews, observations, and documentstudies. Based on the research conducted, the existence of Islamic Boarding Schools has an impact on thecommunity’s economy. Initially, the economic condition was very poor, so with the presence of the communitydevelopment agency, the Annuqayah Islamic Boarding School can provide education, training, and provide capitalfor community businesses and also use the land for profit. Therefore, the environment in the Annuqayah IslamicBoarding School is the main attraction of the pesantren by using the culture since the first that has been applieduntil now. The culture is like nyabis, mutual respect, mutual cooperation, etc.Keywords: pesantren, halal tourism, local wisdom, economy